Vibrational Analysis of the Raman Spectra of Trifluorohalomethanes - Arora, U.S.; Chopra, J.R. (Asian Journal of Chemistry, 2010)
The general valence force field (GVFF), has been used to reinvestigatethe force constants for trifluorohalomethanes. Corioliscoupling constants, centrifugal distortion constants, bond order andbond polarizability derivatives are also computed. In addition tothis the relationship between stretching force constant and otherparameters are also worked out.